Toward a Drone Accountability Regime. Issue 1 (23rd February 2015) - Buchanan, Allen; Keohane, Robert O.
Abstract : From a moral standpoint, lethal drones are intrinsically no worse as a means of warfare than bombing or sending commandos to kill enemies. From the perspective of their users, they have six major advantages over more conventional weapons: they are often cheaper; their use can be more readily concealed; they allow for more precise targeting, with the potential for less "collateral damage"; their use can involve less serious infringements of sovereignty than invasion by troops; and they may be less likely to provoke widespread hostile reactions by the population of the country in which they are used than military operations involving troops on the ground. But these advantages generate three major risks: of violating sovereignty, of over-using the military option, and of making it more difficult to identify violations of constraints against targeting noncombatants. To deal with these risks, a Drone Accountability Regime is needed that imposes obligations on states, which in turn would be required to impose them on their agents. Since it would be infeasible to negotiate a treaty-based legal regime at present and for the foreseeable future, the Drone Accountability Regime should be informal and should involve transnational actors as well as states. Its key principle should be transparency, helping enable civil society to hold states accountable, and its central agent would be an Ombudsperson with broad authority to investigate situations and publicize her findings. No institution can ensure that states, or operators, are held fully accountable to appropriate standards of conduct, but such a regime could increase the degree of accountability for the use of lethal drones.